Pelaksanaan Kegiatan Apel Pagi Dalam Membentuk Karakter Disiplin Siswa - Suprapni, Yayan; Zuhdiyah; Padli (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2025)
This study tries to provide a thorough explanation of why employing apple activities is a beneficial way to help kids build their character and discipline. The morning apple will assist children in forming disciplined habits because it incorporates a number of activities and routines, such as marching, school property completion, and early arrival. Regularly implementing morning apple activities 15 to 20 minutes prior to the start of class is recommended. This study uses qualitative descriptive research techniques, collecting information via conservation, interviews, and documenting. By seeing and participating firsthand in fieldwork, researchers gather data. Researchers employ procedures like member check, triangulation, and extended observations to assess the validity of the data and make sure it is credible. Based on the data and information gathered, researchers came to the conclusion that morning apple routines are a useful tool for forming students' disciplined character and are reinforced by a variety of morning apple activities. Good examples of discipline from teachers, student intention and awareness, student enthusiasm to follow morning apples, and adequate facilities are the supporting factors of morning apple activities in developing the character of student discipline. On the other hand, the outside environment, long student travel distances, bad weather, and a lack of parental encouragement in the application of discipline are the inhibiting factors.